Bovine Tuberculosis Case Intervention Using the T.SPOT.TB Assay to Screen Dairy Workers in Bailey County, Texas - Rodriguez, Anabel; Douphrate, David; Gimeno Ruiz de Porras, David; Prot, Emilie; Perez, Adriana; Hagevoort, Robert; Nonnenmann, Matthew (Frontiers in Public Health, 2020)
Abstract Background: One potential exposure on a dairy farm is Mycobacterium bovis or bovine tuberculosis (bTB)—an infectious zoonotic pathogen. The prevalence of tuberculosis among dairy workers in the U.S. is unknown largely due to insufficient surveillance and testing practices. Our objective was to determine the prevalence and risk factors of LTBI among dairy workers potentially exposed to cattle infected with bTB in two Bailey County, Texas dairy farms in 2016. Methods: This study involved a secondary analysis of data that were collected by Texas State Department of Health Services (DSHS) Public Health Region 1 (PHR 1). A total of 140 dairy workers were tested using the T.SPOT.TB test assay. As a proxy for occupational exposures, we used three categories of cattle exposure groups based on activity, duration, and conditions of exposure to cattle—high, medium, low. Results: Positive LTBI was found among 14/140 (10.0%) of the dairy workers tested with 12/87 (13.8%) in Dairy A and 2/53 (3.8%) in Dairy B. All LTBI cases were determined to be from Hispanic workers with 71.4% indicating having been vaccinated with the BCG vaccine in their country of birth and none indicated previously known exposure to TB. The high category of cattle exposure group experienced a the highest prevalence of LTBI (64.3%), followed by the medium cattle exposure group (28.6%), and the low cattle exposure group (7.1%). Conclusion: Our findings suggest that the prevalence of LTBI among dairy workers in Bailey County, Texas is higher than demographically comparable workforces. Future efforts should focus on the development, delivery, and evaluation of a tuberculosis—and other zoonotic diseases—health and safety training which can become a part of a more comprehensive safety management and training program on dairy farms.